Pozycja społeczna nauki w Wielkopolsce - Stankowski, Jan; Ziembiński, Zygmunt (Wydział Prawa i Administracji UAM, 1992)
The article offers a short presentation of the history of rise of scientific institutions in Wielkopolska, as well as the role and social function of those institutions, now and in the past.
Social status of science in Wielkopolska